دراسة بيولوجية لأنواع خنافس البذور من الجنس Callosobruchus (Coleoptera :Bruchidae) وتسجيل أحد طفيلياتها - محرز, سلمان محرز; احسان, سليمان احسان ابراهيم (Latakia University Journal -Biological Sciences Series, 2013)
أجريت الدراسة المخبرية خلال العام 2010 لبيولوجيا خنافس البذور الآتية: Callosobruchus chinensis وC. maculatus وC. analis (Bruchidae: Coleoptera) على بذور العدس للنوع الأول والحمص للنوعين الآخرين، وتبين أن لها 10 و8 و5 أجيال - على التوالي - خلال فترة النشاط التي امتدت (من شهر آذار حتى شهر تشرين الثاني للنوع الأول والثاني ومن شهر نيسان حتى شهر تشرين الأول للنوع الثالث). وضعت أنثى النوع C. maculatus 100.29 ± 18.26 بيضة خلال 11.14 ± 0.64 يوماً من حياتها على حين وضعت أنثى النوع C. chinensis 83.29 ± 6.32 بيضة خلال 6.43 ± 0.49 يوماً ووضعت أنثى النوع C. analis 75.29 ± 9.05 بيضة خلال 6.71 ± 0.70 يوماً. يستغرق التطور من مرحلة البيضة إلى مرحلة الحشرة البالغة 25.87 ± 3.29 و31.43 ± 5.09 و35.36 ± 3.49 يوماً - على التوالي - لتلك الأنواع تحت الظروف البيئية للمخبر. لم يلاحظ أي اختلاف في مدة التطور بين الذكور والإناث عدا لدى النوع C. maculatus فقد انبثقت الذكور قبل الإناث بحوالي 12 ساعة. كانت النسبة الجنسية (ذكور:إناث) أكبر لصالح الإناث من الذكور في النوع C. chinensis (1: 1.1) ، وأكبر لصالح الذكور من الإناث في النوع C. maculatus (1.1: 1)، ومتساوية في النوع C. analis (1:1). تم تسجيل الدبور المتطفلAnisopteromalus calandrae (Howard, 1881) (Pteromalidae: Hymenoptera) على النوع C. maculatus للمرة الأولى في سوريا. A Laboratory study was conducted during 2010 on the biology of seed beetles: Callosobruchus chinensis, C. maculatus and C. analis (Coleoptera: Bruchidae) on lentil seeds for the first specie and chickpea seeds for the last two species. These beetles completed 10, 8 and 5 generations respectively when they were active (from March to November for the first and second species and from April to October for the third species ). C. maculatus laid an average of 100.29 ± 18.26 eggs over a period of 11.14 ± 0.64 days, C. chinensis laid 83.29 ± 6.32 eggs over 6.43 ± 0.49 days and C. analis 75.29 ± 9.05 eggs over 6.71 ± 0.70 days. The total development process from egg to adult takes an average of 25.87 ± 3.29, 31.43 ± 5.09 and 35.36 ± 3.49 days respectively for species under the ambient laboratory conditions. There was no difference in the development time between males and females except for C. maculatus, where the male emerged about twelve hours before the female. Sex ratio (male: female) was more in favour of female than male in C. chinensis (1: 1.1) and more in favour of male than female in C. maculatus (1.1: 1), but equal in C. analis (1: 1). The parasite wasp Anisopteromalus calandrae (Howard, 1881) (Hymenoptera: Pteromalidae) could be considered the first recorded on C. maculatus in Syria.